Kajian Hukum Tata Ruang Sengketa Tanah Warga Terhadap Kepentingan Masyarakat Luas (Studi Kasus: Pengembangan Jalan Tol Trans Sumatera Lampung) - Insan, Isep H; Chryzalmantia, Vavella; Khodijah, Siti; Ningrum, Sevti Prana; Brahmana, Rizkita (Peneliti.net, 2024)
Land as a social asset is a means of binding unity among the social environment for life and living, while land as a capital asset is as capital in development and has grown as a very important economic object as well as a material for commerce and an object of speculation. Development activities, especially development in the material sector both in cities and villages, require a lot of land as a shelter for development activities. This research aims to examine the spatial legal perception of land disputes against the public interest of outsiders. The typology of this research is descriptive analysis which aims to describe, inventory, and analyse the actual conditions of the study of spatial law to resolve land disputes through library research (library reseach) with emphasis on secondary data sources. The results of the study of Law Number 26 of 2007 concerning Spatial Planning are the legal basis for the government to organise space in the context of national development. Land disputes that occur due to spatial planning issues can involve the government, private parties, and the community. The court is an institution that can resolve land disputes in various ways, such as mediation or through court decisions. Therefore, it is important for communities to understand the legal basis of spatial planning in order to protect their land ownership rights.